2002
DOI: 10.3354/cr023001
|View full text |Cite
|
Sign up to set email alerts
|

Revised 21st century temperature projections

Abstract: Temperature projections for the 21st century made in the Third Assessment Report (TAR) of the United Nations Intergovernmental Panel on Climate Change (IPCC) indicate a rise of 1.4 to 5.8°C for 1990-2100. However, several independent lines of evidence suggest that the projections at the upper end of this range are not well supported. Since the publication of the TAR, several findings have appeared in the scientific literature that challenge many of the assumptions that generated the TAR temperature range. Inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is possible that models overestimate the rise (fall) of a given climate element and underestimate the impact of certain factors on climate. Other authors also noted that the temperature projections reported by the IPCC in its reports were overestimated, especially for the more extreme variants (Michaels et al, 2002;Ongoma et al, 2018). The uncertainties of climate models was discussed in the work of Laprise et al (2008), Holtanová et al (2014), Sanderson et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that models overestimate the rise (fall) of a given climate element and underestimate the impact of certain factors on climate. Other authors also noted that the temperature projections reported by the IPCC in its reports were overestimated, especially for the more extreme variants (Michaels et al, 2002;Ongoma et al, 2018). The uncertainties of climate models was discussed in the work of Laprise et al (2008), Holtanová et al (2014), Sanderson et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this hot running were discussed. The simple model, using parameter values consistent with a growing body of papers [e.g., 733] that report climate sensitivity to be below current central estimates, showed that in at least five significant respects the general-circulation models’ approach was questionable:The assumption that temperature feedbacks will double or triple direct warming is unsound. Feedbacks may well reduce warming, not amplify it (see, e.g., [16, 19]).…”
Section: Introductionmentioning
confidence: 99%
“…Two basic pressures are usually implicated in such events: climatic change (e.g. Malhi, 2002;Michaels et al, 2002;Reay, 2002;Greenland et al, 2003) and changes in agricultural land-use resulting in massive inputs of fertilisers, regular mechanised disturbance (biotope degradation), and the concomitant replacement of relatively unproductive, undisturbed habitats with highly productive and highly disturbed ones (Ratcliffe, 1984;Hodgson, 1986).…”
Section: Introductionmentioning
confidence: 99%